Canopy architectural and physiological characterization of near-isogenic wheat lines differing in the tiller inhibition gene tin - Moeller, Carina; Evers, Jochem B.; Rebetzke, Greg (Frontiers in Plant Science, 2014)
Tillering is a core constituent of plant architecture, and influences light interception to affect plant and crop performance. Near-isogenic lines (NILs) varying for a tiller inhibition (tin) gene and representing two genetic backgrounds were investigated for tillering dynamics, organ size distribution, leaf area, light interception, red: far-red ratio, and chlorophyll content. Tillering ceased earlier in the tin lines to reduce the frequencies of later primary and secondary tillers compared to the free-tillering NILs, and demonstrated the genetically lower tillering plasticity of tin-containing lines. The distribution of organ sizes along shoots varied between NILs contrasting for tin. Internode elongation commenced at a lower phytomer, and the peduncle was shorter in the tin lines. The flag leaves of tin lines were larger, and the longest leaf blades were observed at higher phytomers in the tin than in free-tillering lines. Total leaf area was reduced in tin lines, and non-tin lines invested more leaf area at mid-canopy height. The tiller economy (ratio of seed-bearing shoots to numbers of shoots produced) was 10% greater in the tin lines (0.73–0.76) compared to the free-tillering sisters (0.62–0.63). At maximum tiller number, the red: far-red ratio (light quality stimulus that is thought to induce the cessation of tillering) at the plant-base was 0.18–0.22 in tin lines and 0.09–0.11 in free-tillering lines at levels of photosynthetic active radiation of 49–53% and 30–33%, respectively. The tin lines intercepted less radiation compared to their free-tillering sisters once genotypic differences in tiller numbers had established, and maintained green leaf area in the lower canopy later into the season. Greater light extinction coefficients (k) in tin lines prior to, but reduced k after, spike emergence indicated that differences in light interception between NILs contrasting in tin cannot be explained by leaf area alone but that geometric and optical canopy properties contributed. The careful characterization of specifically-developed NILs is refining the development of a physiology-based model for tillering to improve understanding of the value of architectural traits for use in cereal improvement.